Diagnostic use of endoscopic full‐thickness wall resection (eFTR)—a novel minimally invasive technique for colonic tissue sampling in patients with severe gastrointestinal motility disorders. Issue 1 (6th July 2017) - Valli, P. V.; Pohl, D.; Fried, M.; Caduff, R.; Bauerfeind, P.
Abstract: Background: Complex gastrointestinal (GI) motility disorders such as chronic intestinal pseudo‐obstruction (CIPO) or Hirschsprung's disease (HD) are challenging to diagnose and treat appropriately. Thorough assessment of patient history, radiographic exams, endoscopy, and motility measurements aid in diagnostic workup, yet underlying histology is the cornerstone to enable a more distinct diagnosis of neuromuscular GI disorders. Traditionally, surgical procedures have been performed to obtain specimen suitable for accurate histologic analysis. Methods: We performed endoscopic full‐thickness resection (eFTR) using a full‐thickness‐resection device (FTRD) under moderate propofol sedation in four patients with suspected severe neuromuscular gut disorders including CIPO. Key Results: The mean age of the four patients was 43 y (range 19‐56 y). Technical and histological success providing large colonic full‐thickness tissue samples of excellent quality was achieved in all four patients (success rate 100%). The mean procedure time was 12 min (range 5‐20 min). The mean diameter of the resected specimen was 21 mm (range 20‐22 mm). No adverse events connected to the procedure itself occurred. Histology ranged from aganglionosis such as Hirschsprung's disease (HD) to hypoganglionosis and eosinophilic leiomyositis combined with lymphocytic ganglionitis in a third patient. Histology was unspecific in one patient. Conclusion and Inferences: EFTR allows safe and minimal invasive harvesting of ample full‐thickness tissue samples for accurate histological analysis in patients with suspicion of neuromuscular gut disorders. Abstract : The diagnosis of neuromuscular gut disorders such as chronic intestinal pseudo‐obstruction (CIPO) or Hirschsprung's disease (HD) is challenging and we lack safe and efficient methods to acquire ample tissue samples for histological analysis. We were able to show in four patients that diagnostic full‐thickness resection (eFTR) provides sufficient (mean diameter 21 mm) and high‐quality tissue samples to further diagnose neuromuscular gut disorders. EFTR represents a new and safe technique to easily harvest full‐thickness gut samples for diagnostic purposes.